The development of guided inquiry-based mathematics student’s worksheet on algebra material in eighth grade students in SMP / MTs in Landak Regency - Annur, Muhammad Firman; Annurwanda, Pradipta; Suprihatiningsih, Siti (Unnes Journal of Mathematics Education, 2018)
This research is motivated by the lack of practical use of student worksheets in schools. This research is development research. The product developed and tested in the form of guided inquiry-based worksheets on Algebra material for eighth grade MTs students. The development model used is ADDIE (Analysis, Design, Development, Implementation, Evaluation). The purpose of this research is to develop guided inquiry-based worksheets that fulfill the aspects of validity, practicality, and effectiveness to help class VIII MTs to better understand the algebraic material. The subject of this study was the eighth-grade students of MTs 1 Landak. The instruments used were validation sheets, observation sheets, and learning outcome tests. The results of instrument validation are categorized as valid with the level of material validation of 76.25% and media validation of 78.7%. The results of LKS implementation observations found a practical level of 78.3%. Learning test results students find an average test of learning outcomes obtained by students of 77.7 with a percentage of classical completeness of students by 80%. The results of this test indicate that LKS is included in the sufficient category.